DESIGN OF DESCRIPTION STORIES AS EDUCATIONAL MEDIA FOR MUSLIMAH CLOTHES FOR EARLY CHILDREN - Nurhalima Nurhalima; syafwan syafwan (Universitas Negeri Padang, 2020)
In Islamic muslim dress called a hijab serves to cover the body parts that are forbidden to see or other words aurat. In Indonesia there are still adult women wearing muslim clothing that is not true, and also can not distinguish between a hijab and a veil, it also occurs in children of an early age, where parents have not taught dress muslimah (hijab) to her son. Then by it, the purpose of this design is to produce the design illustrated story books as a medium of education muslim clothing for children of early age due to see there are still mature women wearing muslim clothing, which is not true.The method used in this design is descriptive method of qualitative analysis, where this analysis is carried out based on the logic and arguments of a scientific nature, so as to produce the design illustrated story books that can accommodate and nurture the life of will be education and training for the child to recognize how to clothing a muslim in accordance with Islamic teachings.In the process of solving the problem, used the analysis of the 5W+1H (what, who, where, when, why, and how) to determine the design objectives, the target audience, and the method of solving the problem. The design of this picture-story book entitled “ Yuk Berhijab With the Fig and the Umma” by applying the story descriptive approach to convey his message. the visual message consists of a figure of girls named Fig and his mom called the Umma. Illustration and layout done with the rough sketch, and then visualized in a digital form. For supporting the main media, created supporting media, namely, E-Books, Posters, Pins, Banners, X-Banners, Stickers, and Mugs.Keywords: Books, Picture Stories, Education, Muslim Clothing, EarlyChildhood